2015
DOI: 10.1016/j.tdj.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation of CAD/CAM zirconia-based crown during fabrication steps

Abstract: Background: Excessive marginal discrepancy of crowns favors the rate of cement dissolution and microleakage that may cause pulpal inflammation. Besides, it may increase plaque retention leading to the onset of periodontal disease. Therefore, this research was carried out to study the effect of fabrication stages and artificial aging on the marginal adaptation of CAD/CAM Zirconia-based crowns which have become increasingly popular among the patients due to their natural esthetics and excellent strength.Purpose:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
13
1
Order By: Relevance
“…Although the critical temperature of zirconia aging suggested above 100°C. (El-Dessouky et al, 2015) Also a similar study done by Khaled et. Al to assess the effect of ageing on zirconia crowns using ROBOTA chewing simulator with 49 N chewing forces for 75000 cycles (6 months clinical condition), it was found that there is increase of marginal gap measurements after aging , from (31.41±5.9)µm to (95.28±9.2) µm of Bruxzir crowns.…”
Section: Discussionmentioning
confidence: 61%
“…Although the critical temperature of zirconia aging suggested above 100°C. (El-Dessouky et al, 2015) Also a similar study done by Khaled et. Al to assess the effect of ageing on zirconia crowns using ROBOTA chewing simulator with 49 N chewing forces for 75000 cycles (6 months clinical condition), it was found that there is increase of marginal gap measurements after aging , from (31.41±5.9)µm to (95.28±9.2) µm of Bruxzir crowns.…”
Section: Discussionmentioning
confidence: 61%
“…52 The results of present study were agreed by El-Dessouky et al who showed that thermo-mechanical loading has significantly increased the marginal gap measurements when carried out in temperatures between 5°C and 55°C. 53 However, Wael et al assumed that the marginal discrepancies had no significant changes after artificial ageing. 54 However, all results of vertical marginal gap in this study were within the acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…Other study was found, that, the thermomechanical loading increased the vertical marginal gap due to the luting cement. Some parts of the cement film were washed out during the aging procedures, particularly, when using water-soluble cement such as glass-ionomer (26) . On contrary, no significant effect on marginal discrepancy after aging was reported by others (27) .…”
Section: Discussionmentioning
confidence: 99%